“FROM POLICY TO PRACTICE: THE ROLE OF LEADERSHIP IN ACHIEVING GENDER EQUALITY IN EDUCATIONAL INSTITUTIONS” (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2026)
This paper examines the crucial role of educational leadership in transforming gender equality policies into tangible institutional practices. Although many education systems, including those in Uzbekistan, have adopted national frameworks promoting gender equity, the implementation of these policies often remains symbolic. The study explores how leaders particularly rectors, deans, and school principals can bridge the gap between legislative intent and institutional reality through inclusive decision-making, mentorship, and culture-building. It argues that leadership functions not only as an administrative mechanism but also as a moral and transformative force that shapes organizational values and behaviors.